House of monstrous women - Fama, Daphne (Berkley, 2025)
"A young woman is drawn into a dangerous game after being invited to the mazelike home of her childhood friend, a rumored witch, in this gothic horror set in 1986 Philippines. Josephine del Rosario feels like a pariah in her town. Long orphaned after her father's political campaign ends in tragedy, she's all alone taking care of the family home while her older brother is off in Manila, where a revolution brews. And it's starting to feel like he's abandoning her. When she receives a letter from her cherished childhood friend Hiraya, inviting her to play a game, she jumps at the reason to leave town. Josephine will have whatever her heart desires if she wins. Maybe Josephine can change her life. It doesn't matter that dark rumors have always surrounded Hiraya. Except Hiraya's house is strange...labyrinthine and huge and something seems to be following Josephine everywhere she turns. What's worse is there's something her old friend isn't telling her. There's something insidious about this invitation, and if Josephine isn't careful, she'll find that change is sometimes bought with blood"--